2018
DOI: 10.1080/10803548.2018.1502131
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian network model to diagnose WMSDs with working characteristics

Abstract: It was verified that working characteristics, such as working hours and pace, impact the incidence rate of WMSDs, and a BN model was developed to probabilistically diagnose WMSDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Interestingly, the available literature data demonstrated that the prevalence of these disorders in specific working populations and/or occupational sectors is significantly higher than in general population [3] showing a causal relationship between different types of occupational risk factors (e.g. awkward positions, repetitive movements, low temperatures, manual handling of heavy loads, prolonged computer work, mechanical vibrations, work-related stress) and the development of MSDs that, in this context, are defined as Work related Musculoskeletal Disorders (WMSDs) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the available literature data demonstrated that the prevalence of these disorders in specific working populations and/or occupational sectors is significantly higher than in general population [3] showing a causal relationship between different types of occupational risk factors (e.g. awkward positions, repetitive movements, low temperatures, manual handling of heavy loads, prolonged computer work, mechanical vibrations, work-related stress) and the development of MSDs that, in this context, are defined as Work related Musculoskeletal Disorders (WMSDs) [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the development and validation of a new assessment tool remain pertinent. According to the previous researches, [19][20][21] heavy physical work, high psychosocial work demands and the presence of comorbidities were risk factors that had at least reasonable evidence for the development of WMSDs. Smoking and body mass index were considered risk factors too.…”
Section: Resultsmentioning
confidence: 99%
“…Experts' knowledge and some algorithms are utilized for creating the casual structure of BN. Prior information and experts' knowledge can help structure learning, support parameters learning, prevent from overfitting and work with incomplete data as well (Ahn et al , 2018). However, many papers ignore these capabilities.…”
Section: Introductionmentioning
confidence: 99%